Metaphor in Marketing Language - Inga DRUȚĂ; Lidia VIERU; Mariana VLAS (Philologia, 2023)
From Aristotle to Roman Jakobson to George Lakoff, Mark Johnson and others, the concept of metaphor has undergone substantial changes. This paper deals with conceptual metaphor in marketing language. At the heart of metaphorical conceptualisations are mappings between different conceptual domains, linking a newer or more complex, more abstract domain with a more familiar or simpler, more accessible one. In addition to denotative terms, a vast network of conceptual metaphors operates in marketing language, helping to shape and understand its key concepts. The most numerous category of conceptual metaphors are created with the key marketing variables of product, brand, consumer, enterprise and promotion as their reference points. The most common metaphors in marketing language are the living organism metaphor, the war metaphor (including the sports metaphor), the anthropomorphic metaphor, the medical metaphor. Metaphor is not an isolated phenomenon, but a resource used systematically in marketing language, with a substantial role in building the economic reality of the field, facilitating the understanding of abstract and complex marketing concepts by analogy with familiar areas of experience.